Factor structure of the Me as A Parent scale in a community sample of Portuguese mothers - Marques,Teresa (2020)
This study aimed to examine the factor structure of the Portuguese version of a parental self-regulation measure: "Me as a Parent" (MaaP). A confirmatory factor analysis was conducted with an online convenience sample of 370 mothers of children aged between 3 and 15 (M = 9, SD = 3.74). Results showed that in this sample, the original structure of the MaaP was not confirmed. The revised model with three first-order factors showed good fit indices, χ2 = 202.37, p < .001, χ2/df = 101, CFI = .92, TLI = .91; SRMR = .05, RMSEA = .05, 90% CI = (0.046, 0.063). The factors of MaaP showed good internal consistency, except for Personal Agency. The instrument achieved discriminant validity and showed good test-retest reliability. Although the MaaP seems to be a promising measure, the present results show that more research is needed to validate this new scale.